Educational Processes and Learning at Home During COVID-19: Parents’ Experiences with Distance Education - Demir, Mehmet Raci; Yildizli, Hülya (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
Due to the lockdown measures and severe restrictions taken to reduce COVID-19 transmission, which has globally been inflicted on people since March 2020, a new type of education in the form of online homeschooling has brought the role of parents to the forefront. Using online semi-structured interviews, this study aimed to investigate parents’ views on the implementation of distance education during COVID-19 in Istanbul, Turkey. The data obtained from parents with different socioeconomic backgrounds and whose children were at public and private schools were coded using initial, process, and emotion qualitative coding techniques. The data were categorized into three main themes: beginning of distance education, process of distance education, and outcomes of distance education. The beginning theme was further analyzed under three subcategories: problems related to the child, problems related to parents, and problems related to public schools. The problems encountered during the process of distance education were investigated under three subheadings: problems related to the child’s academic and social life, problems related to parents, and problems related to parent–child relationships. Data under the main theme, outcomes of distance education, were defined as positive or negative outcomes in terms of the child and parents. Results revealed that at the beginning of the process, during the process, and during the outcomes of distance education, parents experienced problems with digital technology, the new education model, teachers, themselves, and their children, as well as economic, social, and psychological problems. Parents also had various constructive suggestions about distance education during COVID-19.